The N1038S Substitution and 1153EQTRPKKSV1162 Deletion of the S2 Subunit of QX-Type Avian Infectious Bronchitis Virus Can Synergistically Enhance Viral Proliferation - Li, Shuyun; Fan, Shunyi; Li, Nianning; Shen, Yuxi; Xiang, Xuelian; Chen, Wen; Xia, Jing; Han, Xinfeng; Cui, Min; Huang, Yong (Frontiers in Microbiology, 2022)
The S2 subunit of IBV plays a critical role in the process of IBV infection. A comparison between the S2 subunit sequence of chicken embryo kidney cell (CEK) adapted virulent QX-like IBV strain SczyC30 （hereafter referred to as zy30） and its CEK-attenuated strain, SczyC100, revealed an N1038S substitution in S2 subunit and a 1154EQTRPKKSV1162 residue deletion in the C-terminus of the S2 subunit. In order to explore whether these two mutations are related to changes in the biological characteristics of IBV, we firstly constructed an infectious clone of zy30 using a bacterial artificial chromosome (BAC), which combines the transcription of infectious IBV genomic RNA in non-susceptible BHK-21 cells with the amplification of rescued virus rzy30 in CEK cells. Then, three recombinant viruses, including an rzy30S2-N1038S strain that contained the N1038S substitution, an rzy30S2-CT9△ strain that contained the 1154EQTRPKKSV1162 deletion, and an rzy30S2-N1038S-CT9△ strain that contained both mutations, were constructed using rescued virus rzy30 as the backbone. The results showed that each mutation did not significantly affect the replication titer in CEK cells, but reduced pathogenicity in chickens, while in combination, the N1038S substitution and 1154EQTRPKKSV1162 deletion improved the proliferation efficiency in CEK cells and reduced pathogenicity, compared to rzy30 strain. The contribution made by the 1154EQTRPKKSV1162 deletion in reducing pathogenicity was higher than that of N1038S substitution. Our results revealed that the N1038S substitution and 1154EQTRPKKSV1162 deletion in S2 subunit were deeply involved in the replication efficiency of IBV and contributed to reduction of viral pathogenicity.